Poorly differentiated chordoma showing loss of SMARCB1/INI1: Clinicopathological and radiological spectrum of nine cases, including uncommon features of a relatively under-recognized entity - Rekhi, Bharat; Michal, Michael; Ergen, Fatma Bilge; Roy, Paromita; Puls, Florian; Haugland, Hans Kristian; Soylemezoglu, Figen; Kosemehmetoglu, Kemal (Annals of diagnostic pathology, 2021)
Poorly differentiated chordoma is a newly recognized entity in the recent World Health Organization (WHO) classification of tumors of soft tissue and bone. Slightly over 60 such cases have been documented. Herein, we present a clinicopathological profile, including radiological features, of nine cases, which occurred in five males and four females, with age varying from 1 to 29 years (median = 43), in the cervical spine (n = 2), skull base (n = 2), clivus (n = 2), thoracic spine (n = 1) lumbar spine (n = 1) and coccyx (n = 1) Average tumor size was 4.8 cm. None of the 6-referral cases was diagnosed as a poorly differentiated chordoma at the referring laboratory. Histopathologically, all cases displayed a cellular tumor comprising polygonal cells (n = 9) displaying moderate to marked nuclear pleomorphism with prominent nucleoli (n = 7), eosinophilic (n = 9) to vacuolated cytoplasm (n = 7), rhabdoid morphology (n = 4), interspersed mitotic figures (n = 5), focal necrosis (n = 6) and inflammatory cells (n = 9). A single tumor displayed areas resembling classic chordoma, transitioning into poorly differentiated areas. There were multinucleate giant cells and physaliphorous cells in two tumors, each, respectively. Immunohistochemically, tumor cells were positive for AE1/AE3 (7/7), EMA (7/7), cytokeratin (CK) MNF116 (1/1), OSCAR (1/1), brachyury (9/9, diffusely), S100P (4/7, mostly focally), and glypican 3(2/4). SMARCB1/INI1 was completely lost in all nine tumors. A single case tested by FISH showed homozygous deletion of the SMARCB1 gene. Therapeutically (n = 7), all patients were treated with surgical resection (invariably incomplete) (n = 5), followed by adjuvant radiation therapy (n = 4) and chemotherapy (n = 4). While a single patient partially responded to treatment and another patient is alive with no evidence of disease after 23 years, three patients died of disease, six, eight, and 11 months post-diagnosis, despite adjuvant treatments. A single patient presented with a metastatic lung nodule, while another developed widespread metastasis. Poorly differentiated chordomas display a spectrum of features, are associated with a lower index of suspicion for a diagnosis, and display aggressive outcomes. Critical analysis of radiological and histopathological features, including necessary immunostains (brachyury and SMARCB1/INI1), is necessary for their timely diagnosis. These tumors show loss of SMARCB1/INI1 immunostaining and homozygous deletion of INI1/SMARCB1 gene.
Keywords: dospělí; metastázy nádorů; sekvenční delece; Female; Infant; Chordoma; dítě; předškolní dítě; Adult; ženské pohlaví; Adolescent; Immunohistochemistry; lidé; imunohistochemie; Male; nádorové biomarkery; kojenec; Child, Preschool; gen SMARCB1; chordom; Biomarkers, Tumor; Child; mužské pohlaví; Neoplasm Metastasis; SMARCB1 Protein; Sequence Deletion; mladiství; Humans